Senescence-associated secretory phenotype and its impact on oral immune homeostasis - Yue, Ziqi; Nie, Lulingxiao; Zhao, Pengfei; Ji, Ning; Liao, Ga; Wang, Qi (Frontiers in Immunology, 2022)
The senescence-associated secretory phenotype (SASP), which accumulates over the course of normal aging and in age-related diseases, is a crucial driver of chronic inflammation and aging phenotypes. It is also responsible for the pathogenesis of multiple oral diseases. However, the pathogenic mechanism underlying SASP has not yet been fully elucidated. Here, relevant articles on SASP published over the last five years (2017–2022) were retrieved and used for bibliometric analysis, for the first time, to examine SASP composition. The results demonstrated the roles of SASP in oral diseases and oral cells. More than half of the relevant articles focus on various cytokines (27.5%), growth factors (20.9%), and proteases (20.9%). In addition, lipid metabolites (13.1%) and extracellular vesicles (6.5%) have received increasing attention over the past five years, and have been recognized as novel SASP categories. Based on this, we summarize the evidences demonstrating that SASP plays a pleiotropic role in oral immunity and propose a four-step hypothetical framework for the progression of SASP-related oral pathology—1) oral SASP development, 2) SASP-related oral pathological alterations, 3) pathological changes leading to oral immune homeostasis disruption, and 4) SASP-mediated immune dysregulation escalating oral disease. By targeting specific SASP factors, potential therapies can be developed to treat oral and age-related diseases.